Mathematical model to determine the profitability of crops in the state of Hidalgo (Research, Society and Development, 2026)
The agricultural sector in the state of Hidalgo faces several challenges stemming from price volatility and the decline in trade agreements related to barley production, a crop closely linked to the brewing industry. Given this context, the objective of this study is to evaluate the profitability of alternative crops to barley that can support agricultural producers' decision-making. To this end, moving average and simple exponential smoothing forecasting models were applied to estimate the annual production of barley, oats, sorghum, and wheat, as well as an optimization model based on linear programming, considering constraints on agricultural land availability, seed availability, and investment amount. The proposed model was solved using Lingo 19.0 software and applied to representative municipalities in the state of Hidalgo, primarily those located in the Altiplano hidalguense. The results obtained indicate that crops such as sorghum and oats represent viable and profitable alternatives for the study region, due to their low production costs and their good adaptation to the region's climatic and irrigation conditions, without completely ruling out barley production in those municipalities where it remains strategic. It is concluded that the use of optimization tools is useful in supporting decision-making to improve the profitability of agricultural production in the highlands, allowing for a reduction in dependence on a single crop and mitigating the risks associated with market uncertainty.